Франків поетичний цикл «Скорбні пісні»: аспекти поетики - Швець, А. (Слово і Час, 2021)
У статті комплексно проаналізовано Франків поетичний цикл
«Скорбні пісні», який увійшов до другого видання збірки «З вершин
і низин» (1893). Кожен із дев’яти віршів осмислено з погляду генології, образності, художніх засобів, особливостей версифікації, а також
інтертекстуальних паралелей на рівні ремінісценцій та алюзій. Звернено увагу на характер ліричного героя, внутрішній сюжет циклу, хронотопну організацію, лейтмотиви, фольклорні перегуки. Franko’s poetic cycle “Mourning Songs” became the third in his collection “From the
Heights and Lowlands” (1893), however, this cycle was not included in the first edition of
the collection in 1887. Nine lyrical poems of the cycle “Mourning Songs” mainly belong
to the genre of reflective-meditative lyrics, in which the author (lyrical subject) reflects on
social structure, ontological and existential problems. The articulation of the mental state of
the lyrical hero, his inner suff ering, loneliness, social vacuum, feeling of being unwanted in
the world are important motives here. Franko purposely doesn’t arrange poems in chronological order but instead develops
the inner plotline of the cycle with the following motives: guilt for the mournful mood of
his muse, inner rebellion against social evil, apocalyptic vision of destroying the old world
order, declaration of his solidarity with the humiliated, obsession with the idea of service,
emotional despair, resignation and passive reconciliation with one’s own misfortune, statement
of one’s social credo, the experience of loneliness and marginality, optimistic vision of
the earthly paradise against the background of prison-like gloom.
As a result, eschatological motives appear: the domination of evil on earth inevitably
will lead to its destruction for the sake of a new life and restoration of just law and order.
In mood and stylistically, Franko’s jail poetry corresponds to the prison lyrics by Taras
Shevchenko. Each of the nine poems in the cycle has been considered in terms of poetics, genre,
imagery, literary means, versification, as well as intertextual parallels at the level of reminiscences
and allusions. The researcher paid attention to the character of the lyrical hero, the
internal plot of the cycle, chronotopic organization, leitmotifs, folklore structures.
The philosophical meditations of the cycle “Mourning Songs”, perceived in the context
of Franko’s biography, reflect the parallelism of the lyrical hero’s existence and the author’s
psychobiography of the period marked by the first two arrests.